Endovascular treatment for acute M2 occlusion stroke within 6 hours-a retrospective real-world evidence - Xu, Yi; Fu, Wang; Wang, Yongpeng; Bi, Qianqian; Wang, Qiwei; Yang, Lu; Zhang, Quanbin; Wang, Feng (Frontiers in Cardiovascular Medicine, 2023)
Background We compared the efficacy and safety of endovascular therapy (EVT), intravenous (IV) thrombolysis and conservative treatment in M2 segment occlusion stroke based on a real-world database. Methods We retrospectively analysed the database of admitted patients with M2 segment occlusion between January 2018 and December 2020. The patients who were eligible for reperfusion treatment were assigned to EVT, IV thrombolysis or conservative treatment according to the exact management proceeding. The primary outcome was a score of 0 and 1 on the modified Rankin scale (mRS) at 90 days. The odds ratio (OR) for the primary outcome was adjusted for age, baseline National Institute of Health Stroke Scale score, and door-to-treatment time. The secondary outcomes were based on a mRS score from 0 to 2 at 90 days and the safety outcomes including symptomatic intracranial hemorrhage, and all-cause mortality. The data were analysed by the logistical regression model, including baseline adjustments. Results A total of 109 patients were included. Among them, 42 (38.5%) patients received EVT, 45 (42.5%) received IV thrombolysis and 22 (20.8%) received conservative treatment. The primary outcome based on a mRS score of 0 and 1, occurred in 66.7% of patients in the EVT group and 40% in the IV thrombolysis group (adjusted OR, 1.79; 95% confidence interval [CI], 1.19-2.68; P=0.01). Symptomatic intracranial hemorrhage occurred in 1 patient (2.3%) in the EVT group and in 2 patients (4.4%) in the IV thrombolysis group (adjusted OR=0.71, 95% CI: 0.13-4.07). Conclusions EVT showed better functional outcomes than IV thrombolysis and conservative treatment in moderate to severe acute stoke patients with M2 occlusion. There was no significant difference in the three groups concerning the incidence of symptomatic intracranial hemorrhage.